Kaiserwahl und Krönung in Frankfurt am Main 1612 und die böhmische Teilnahme an diesen Ereignissen (Theatrum historiae, 2012)
The author deals with the festivities of imperial election and coronation in Frankfurt am Main in May and June 1612 that brought to the imperial throne Bohemian king Matthias of Habsburg. He analyses political situation at that time and focuses on representative and political treatises that were published in connection with these events all around Europe. The election of king Matthias is explained as a victory of Protestant imperial estates. The author works also with two kinds of sources that have not been used before – a very detailed accommodation list of the Matthias‘ court and a very large documentation of the preparation of the Matthias‘ journey that is preserved in the registry of Bohemian court chancellery (Böhmische Hofkanzlei). Both the sources are minutely analysed and then published as appendices of the article. Finally, the author reflects the role of highest Bohemian chancellor (Obersthofkanzler) Zdenko Adalbert Popel of Lobkowitz in the king‘s delegation that seems to be very illogical according to the previous tense relationship between Lobkowitz and Matthias. He cames to conclusion that Lobkowitz‘s extraordinary position in the royal suite was closely related to the political interests of the Spanish court and it was perhaps one of the conditions that were necessary to be done to change former negative Spanish attitude towards Matthias´ imperial candidacy.
Keywords: Frankfurt am Main; 1612; king Matthias; imperial electio; imperial coronation; Czech nobility; journey to diet; Zdenko Adalbert Popel of Lobkowitz; monarchal representation; political situation; Reichshofkanzlei; monarchal residence; Prague